Advances in machine learning First Asian Conference on Machine Learning, ACML 2009, Nanjing, China, November 2-4, 2009 : proceedings - Asian Conference on Machine Learning (Lecture notes in computer science, 2009)
The First Asian Conference on Machine Learning (ACML 2009) was held at Nanjing, China during November 2–4, 2009.This was the first edition of a series of annual conferences which aim to provide a leading international forum for researchers in machine learning and related fieldsto share their new ideas and research findings. This year we received 113 submissions from 18 countries and regions in Asia, Australasia, Europe and North America. The submissions went through a rigorous double-blind reviewing process. Most submissions received four reviews, a few submissions received five reviews, while only several submissions received three reviews. Each submission was handled by an Area Chair who coordinated discussions among reviewers and made recommendation on the submission. The Program Committee Chairs examined the reviews and meta-reviews to further guarantee the reliability and integrity of the reviewing process. Twenty-nine papers were selected after this process. To ensure that important revisions required by reviewers were incorporated into the final accepted papers, and to allow submissions which would have potential after a careful revision, this year we launched a “revision double-check” process. In short, the above-mentioned 29 papers were conditionally accepted, and the authors were requested to incorporate the “important-and-must” resivions summarized by area chairs based on reviewers ’ comments. The revised final version and the revision list of each conditionally accepted paper was examined by the Area Chair and Program Committee Chairs. Papers that failed to pass the examination were finally rejected.